Ex-Muslims in Singapore : a clash of social realities - Muhammad Hariz Bin Husaini (2018)
Apostates often face persecution from religious communities and also their loved ones. It is paramount that we understand how and why individuals become apostates so that they can receive the proper social support from their families and relevant authorities, minimizing their suffering. Hence, this paper investigates how clashes between the Islamic social reality and other social realities pushes Muslims in Singapore towards apostasy by analyzing the narratives of 35 ex-Muslims in Singapore through Berger and Luckmann’s framework; the social construction of reality. The findings show that the presence of alternative realities, unsuccessful socialization and therapy of the ex-Muslims result in the delegitimization of the Islamic social reality. In addition, the study also found that mindlessness perpetuates the synonymy between race and religion. These findings illustrate the journey that ex-Muslims have undergone and how hatred towards them is misplaced while shedding light onto how other hidden populations might have come about.